Optometric, Phytochemical And Gene Expression Analysis Of Ergastic Crystal Load In Plant Parts Of Purple Amaranth (Amaranthus Cruentus L.) (Applied Biological Research, 2023)
The present work was a trio-experimental approach focused on the omics-based  gene expression pattern for ergastic crystal formation in vegetative parts of  purple amaranth (Amaranthus cruentus) and compared with physio-chemical  estimation methods and optometric image analysis. Plant samples, root (S1),  stem (S2), mature leaf (S3), young leaf (S4), insect attacked leaf (S5), senescent  leaf (S6) were analysed. The gene expression analysis was carried out using qRT PCR for two oxalate synthesizing genes SoGLO and SoOXAC, and two oxalate  degrading genes SoOXO and SoOXDC and the area occupied by calcium oxalate  crystals were plotted with the help of IMAGE J and ZEN 4 software in optometric device and the same was quantified using chemical analysis method.  Transcriptional level analysis of both sets of gene pointed to the regulation of  oxalate levels by complex pathways and could help in generating oxalate-less  hybrids in leafy vegetables. Total oxalate wasestimated to be 20% more in S6  than S1, and ranged from 25.0-50.2 mg 100 g-1sample which falls under high to  very high oxalate permissible content in foods. Area occupied by druse crystals  was maximum in S5, followed by S6 and least was found in S1 ranging from  0.0013-0.0284 µm µm-2sample. Gene expression of SoGLO gene was comparable  to the total oxalate content; whereas the area occupied by CaOx crystals showed variations owing to the presence of soluble oxalate content in it.
Keywords: Amaranthus cruentus; druses; ergastic crystals; gene expression; image analysis; oxalate load; qRT-PCR